2013
DOI: 10.1177/1541931213571007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Predictive Displays on Performance in Driving Tasks with Multi-Second Latency

Abstract: Tele-operation of a Lunar rover from a control station on Earth involves a latency of several seconds due primarily to the finite speed (light-speed) of command and sensor signals, and this latency creates a difficult control task for the human operator. Two predictive displays, which seek to aid viewer perception of present events, were designed and evaluated for the specific task of driving a rover with multi-second latency. These displays provided visual information to the human operator on the rover's real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…For example, augmented reality has been used to assist the human operator in estimating the robot’s actual location. Studies have shown that predictive displays have been helpful for driving tasks with both short delays (approximately 400–1100 ms) (Davis et al, 2010) and multi-second delays (Matheson et al, 2013). Augmented reality has also been used to render 3D video projections and create simulated exocentric views of the robot’s environment that improve teleoperation performance (Ferland et al, 2009; Kelly et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, augmented reality has been used to assist the human operator in estimating the robot’s actual location. Studies have shown that predictive displays have been helpful for driving tasks with both short delays (approximately 400–1100 ms) (Davis et al, 2010) and multi-second delays (Matheson et al, 2013). Augmented reality has also been used to render 3D video projections and create simulated exocentric views of the robot’s environment that improve teleoperation performance (Ferland et al, 2009; Kelly et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the impacts of latency on teleoperation performance, a significant research effort has been made to the design of predictive interface‐based teleoperation systems (Deng & Jagersand, 2003; Dybvik et al, 2020; Ha et al, 2018; Matheson et al, 2013; Ricks et al, 2004; C. Wang et al, 2016; Wilde et al, 2020; Witus et al, 2011; Y. Xiong et al, 2006). These predictive interfaces have attempted to compensate latency through first‐order predictive interfaces that mostly offer the predicted state variables for the period of delay (Artstein, 1982; Manitius & Olbrot, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve consistency between the virtual world and the real world, augmented reality (AR) technology is used, and error calibration technology is used to approximate model matching [15]. Matheson et al [16] verified the performance of the predicted display by driving the rover through an obstacle course with a delay of 3 s. Xia et al [17] introduced virtual fixtures into the model-based remote control system. Zhu et al [18] employed a Kinect camera to create a virtual target object.…”
Section: Introductionmentioning
confidence: 99%